2020
DOI: 10.1177/1065912920960232
|View full text |Cite
|
Sign up to set email alerts
|

Merit, Luck, and Taxes: Societal Reward Rules, Self-Interest, and Ideology in a Real-Effort Voting Experiment

Abstract: When are high earnings considered a legitimate target for redistribution, and when not? We design a real-effort laboratory experiment in which we manipulate the assignment of payrates (societal “reward rules”) that translate performance on a real-effort counting task into pre-tax earnings. We then ask subjects to vote on a flat tax rate in groups of three. We distinguish three treatment conditions: the same payrate for all group members (“equal” reward rule), differential (low, medium, and high) but random pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Some have suggested that the route to decreasing the role of self‐interest is to emphasize the randomness of outcomes (e.g., Gee, Migueis, & Parsa, 2017; Tepe, Vanhuysse, & Lutz, 2020). Agent‐based modeling suggests that distributions of income like the ones in the United States arise from chance factors more than individuals’ abilities or skills (Pluchino, Emanuele Biondo, & Rapisarda, 2018).…”
Section: People's Preferences For Inequality Respond Instantly To Cha...mentioning
confidence: 99%
“…Some have suggested that the route to decreasing the role of self‐interest is to emphasize the randomness of outcomes (e.g., Gee, Migueis, & Parsa, 2017; Tepe, Vanhuysse, & Lutz, 2020). Agent‐based modeling suggests that distributions of income like the ones in the United States arise from chance factors more than individuals’ abilities or skills (Pluchino, Emanuele Biondo, & Rapisarda, 2018).…”
Section: People's Preferences For Inequality Respond Instantly To Cha...mentioning
confidence: 99%